(untitled) (Vietnam Journal of Community Medicine, 2021)
Objective: To describe the expectations of oral health care services of first-year medical students at Hanoi Medical University. Subject and method: A cross-sectional descriptive study was applied with data collection by using online interview. Information of expectations about the elements of oral health care services was recorded and analysis according to the Likert scale. The study was carried out on 574 subjects. Results: Study participants had high expectations in the cleanliness of medical facilities, accounting for 74.56%. Influencing factors of expectations in treatment procedures and treatments were informed about side effects, risks of treatment; were examined on time (mean expected score was 3.9; 3.87, respectively). Study participants have high expectations for all items in communication factors (mean score was above 3.92) and treatment outcomes (mean expected scores are over 3.89). The items with low expectations were the need to give a test/X-ray order, convenient and reassuring medical facility location (mean expected score of 3.45; 3.49 and 3.57 respectively). Conclusion: Most of the study subjects had high expectations about the elements of health care services. In which, the highest expectation belongs to the items of communication between doctor - patient and treatment results.